Detection and characterization of Listeria monocytogenes contamination in raw vegetables - Tang John Yew Huat; Abd Jalil Liyana; Syazwan Razali Nur Amira (E3S Web of Conferences)
Listeria monocytogenes is a psychrophilic bacterium that commonly contaminates and grows in food stored at refrigeration temperature. It can cause serious illness in the elderly, pregnant women, children and immunocompromised individuals. Thus, this study aimed to determine the prevalence of L. monocytogenes in eight selected salad vegetables and characterized antibiotic resistance profiles of L. monocytogenes isolates. A total of 154 salad samples were purchased from four different districts in Terengganu namely Besut, Jerteh, Kemaman and Kuala Terengganu. Samples were enriched with Listeria Enrichment Broth (LEB) at 30˚С for 24 hr before being subjected to selective medium PALCAM agar and PCR and LAMP assays. The L. monocytogenes isolates were tested against seven antibiotics using disk diffusion method. Percentage of L. monocytogenes in samples were detected at 5.19, 3.89 and 3.25% using PCR assay, LAMP assay and plating, respectively. L. monocytogenes isolates showed resistance towards tetracycline, vancomycin, penicillin G and erythromycin. Three isolates have multiple antibiotic resistance (MAR) index higher than 0.2 which indicate the contamination from high-risk or animal sources. It can be concluded that vegetable samples were contaminated with L. monocytogenes that exhibit antibiotic resistance. Consumption of raw vegetables will pose significant risk of foodborne infection.